Headache management—Are we doing enough? An observational study of patients presenting with headache to the emergency department. Issue 3 (22nd April 2004) - Locker, T; Mason, S; Rigby, A
Abstract : Objectives: To identify the causes of acute headache presenting to the emergency department (ED), assess the adequacy of history, examination, and investigation, and determine which clinical features are predictive of secondary headache. Method: A retrospective study of alert (GCS⩾14) patients presenting with headache, to an ED over a one year period. Patients were followed up for three months. The adequacy of history, examination, and investigation were compared with published standards. Analysis using Bayes's theorem determined which clinical features were predictive of secondary headache. Results: Headache in alert patients accounted for 0.5% (n = 353) of new patient episodes, 81.2% (n = 280) of patients had a primary headache disorder. One patient (0.3%) had an adequate history recorded. No patient had a complete examination recorded. Seventy seven (21.8%) patients underwent computed tomography of the head; 80.5% (n = 62) were normal. Lumbar puncture was performed in 23 (6.5%) cases; 18 (78.3%) were normal. A number of clinical features were found to be predictive of secondary headache. Conclusion: Headache is an uncommon symptom in alert patients presenting to the ED. The recorded history, examination, and subsequent investigation do not comply with published standards. A number of predictive features have been identified that may permit the development of a clinical prediction rule to improve the management of this patient group.